E-Commerce AF Parfum System Website Based Using Design Thinking Method - Ritonga, Alda Kharisma; Dewi, Arie Rafika; Rahayu, Eka (Al'Adzkiya, 2021)
Perfume is a fragrance that is produced from the extraction process of aromatic ingredients that are used to provide a fragrant aroma to the human body. E-commerce that develops in the field of information technology that provides convenience and advantages, if compared to conventional sales such as consumers can buy goods online and make it easier for consumers to transact and sellers get large profits because the merchandise is more familiar with the public and can manage data systematic sales.The development method in building AF Perfume E-commerce System is based on the theory of model design thinking. Design thinking is a software development methodology that proposes approaches to solve problems and gather ideas in order to get solutions. The purpose of research writing is to produce a Website-Based AF Perfume E-Commerce System. With the application of this system will facilitate and benefit many parties both consumers and sellers. Keywords: E-Commerce, Parfume, Design Thinking, Website